Resilience to Nested Crises: The Effects of the Beirut Explosion on COVID-19 Safety Protocol Adherence During Humanitarian Assistance to Refugees - Stephanie Nawyn; Ezgi Karaoğlu; Stephen Gasteyer; Rania Mansour; Ali Ghassani; Sandra Marquart-Pyatt; Sandra Marquart-Pyatt (Frontiers Media S.A., 2022)
To provide services safely to refugees during the COVID-19 pandemic, humanitarian non-governmental organizations (NGOs) have instituted public health safety protocols to mitigate the risk of spreading the SARS-CoV-2 virus. However, it can be difficult for people to adhere to protocols under the best of circumstances, and in situations of nested crises, in which one crisis contributes to a cascade of additional crises, adherence can further deteriorate. Such a nested crises situation occurred in Beirut, Lebanon, when a massive explosion in the city injured or killed thousands and destroyed essential infrastructure. Using data from a study on COVID-19 safety protocol adherence during refugee humanitarian assistance in Lebanon, Jordan, and Turkey, we conduct a cross-country comparison to determine whether the nested crises in Beirut led to a deterioration of protocol adherence-the "fragile rationalism" orientation-or whether adherence remained robust-the "collective resilience" orientation. We found greater evidence for collective resilience, and from those findings make public health recommendations for service provision occurring in disaster areas.